Prompt Engineering and Input Art as a Lever for Knowledge Productivity in the Era of Generative Artificial Intelligence: An In-depth Analytical Study in Light of the Latest Experimental Studies and Human-Machine Integration Models - Aljonied, Sakher farea Ghaleb (Universitas Indonesia Mandiri, 2026)
This study investigates the structural transformations in the concept of personal productivity for knowledge workers in light of the increasing dominance of Large Language Models (LLMs), with a particular focus on the